Avaliação do potencial de coagulante recuperado de lodo de ETA para uso em águas de baixa e elevada turbidez - Pedretti, Angela (2022)
Basic sanitation presents itself as a fundamental factor for social development and for guaranteeing public health. Within the services of sanitation, water and its entire system of adduction, treatment and distribution is of fundamental importance. However, the treatment carried out by Water Treatment Plants (WTP) also ends up generating waste whose characteristics come from the quality of raw water and the processes used for its purification. Based on this, this work proposed to carry out a study on the sludge from the WTP of Palmitinho/RS, firstly, through its characterization and verification of aluminum concentrations, due to the coagulation/flocculation process employing the coagulant aluminum sulfate. The feasibility of recovering the coagulant used through the use of the acid extraction process was investigated, observing the possible application of the recovered for the treatment of raw water, with two distinct characteristics: high turbidity and color and low turbidity and color. Regarding the characterization of this sludge, it was observed its need for treatment before disposal, with physical and chemical methods being the most recommended, and that, due to its high concentration of metals, the regeneration of coagulant by acid route presents itself as a viable alternative treatment to be used. The acid extraction process provided a concentration of 683.31 mg/L of aluminum sulfate to the recovered to be used in later tests and a potential to reduce the total volume of the treated sludge by about 45%, evidencing its efficiency. In relation to the tests carried out with the recovered coagulant comparing with commercial coagulant in waters of different turbidity, it was observed that the recovered coagulant, when tested in waters of high turbidity showed a range of applicability superior to the commercial coagulant, showing ≥90% removal in practically all pH ranges. However, the limitation of the use of this recovered coagulant may be related to the color transferred to the water to be treated, since low turbidity water treated with it did not obtain satisfactory results, whereas water with high turbidity obtained also apparent and true color removal efficiencies.